Quantitative measurement of airway dimensions using ultra-high resolution computed tomography - Tanabe, Naoya; Oguma, Tsuyoshi; Sato, Susumu; Kubo, Takeshi; Kozawa, Satoshi; Shima, Hiroshi; Koizumi, Koji; Sato, Atsuyasu; Muro, Shigeo; Togashi, Kaori; Hirai, Toyohiro (Respiratory investigation, 2018)
Quantitative measurement of airway dimensions using computed tomography (CT) is performed in relatively larger airways due to the limited resolution of CT scans. Nevertheless, the small airway is an important pathological lesion in lung diseases such as chronic obstructive pulmonary disease (COPD) and asthma. Ultra-high resolution scanning may resolve the smaller airway, but its accuracy and limitations are unclear. Phantom tubes were imaged using conventional (512 × 512) and ultra-high resolution (1024 × 1024 and 2048 × 2048) scans. Reconstructions were performed using the forward-projected model-based iterative reconstruction solution (FIRST) algorithm in 512 × 512 and 1024 × 1024 matrix scans and the adaptive iterative dose reduction 3D (AIDR-3D) algorithm for all scans. In seven subjects with COPD, the airway dimensions were measured using the 1024 × 1024 and 512 × 512 matrix scans. Compared to the conventional 512 × 512 scan, variations in the CT values for air were increased in the ultra-high resolution scans, except in the 1024×1024 scan reconstructed through FIRST. The measurement error of the lumen area of the tube with 2-mm diameter and 0.5-mm wall thickness (WT) was minimal in the ultra-high resolution scans, but not in the conventional 512 × 512 scan. In contrast to the conventional scans, the ultra-high resolution scans resolved the phantom tube with ≥ 0.6-mm WT at an error rate of < 11%. In seven subjects with COPD, the WT showed a lower value with the 1024 × 1024 scans versus the 512 × 512 scans. The ultra-high resolution scan may allow more accurate measurement of the bronchioles with smaller dimensions compared with the conventional scan.